2015
DOI: 10.1088/0957-4484/26/46/465707
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of biaxial-strained MoS2: sensitive strain dependence and size-dependent reduction rate

Abstract: The effect of biaxial tensile strain on the thermal transport properties of MoS(2) is investigated by combining first-principles calculations and the Boltzmann transport equation. The thermal conductivities of single layer MoS(2) are found to be heavily suppressed by the applied strains; even a moderate biaxial tensile strain, 2 ∼ 4%, could result in a 10 ∼ 20% reduction in the thermal conductivity. Most interestingly, the reduction rate of thermal conductivity is size dependent,which is due to different domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Additionally, our first principles calculations demonstrate that the lattice thermal conductivity decreases with increasing biaxial tensile strain, as shown in Figure S7, in agreement with previous theoretical studies of 2D materials. 12,14,15,17,18 Under biaxial compressive strain, first principles calculations give imaginary phonon modes for bulk In conclusion, the ripple geometry observed here has negligible effect on phonon scattering because the radius of curvatures of the compression-induced ripples in the 2D layers are on the micrometer scale and much larger than both the mean free paths and wavelengths of heat-carrying phonons. In addition, the ripples relax the compressive strain in the top layers, while the tensile strains in the bottom layers are calculated to be insufficient to cause apparent suppression of the thermal conductivity.…”
Section: Main Textmentioning
confidence: 63%
See 2 more Smart Citations
“…Additionally, our first principles calculations demonstrate that the lattice thermal conductivity decreases with increasing biaxial tensile strain, as shown in Figure S7, in agreement with previous theoretical studies of 2D materials. 12,14,15,17,18 Under biaxial compressive strain, first principles calculations give imaginary phonon modes for bulk In conclusion, the ripple geometry observed here has negligible effect on phonon scattering because the radius of curvatures of the compression-induced ripples in the 2D layers are on the micrometer scale and much larger than both the mean free paths and wavelengths of heat-carrying phonons. In addition, the ripples relax the compressive strain in the top layers, while the tensile strains in the bottom layers are calculated to be insufficient to cause apparent suppression of the thermal conductivity.…”
Section: Main Textmentioning
confidence: 63%
“…For example, severe rippling in graphene was shown to generate a long-range scattering potential for electrons and strongly suppress their weak localization. [9][10][11] In addition, the effects of ripples and kinks on thermal conductivity () in 2D materials has been considered in several theoretical studies, including unique strain effects, [12][13][14][15][16][17][18] which can influence the performance and thermomechanical reliability of emerging 2D devices. [19][20][21] Contrary to bulk materials for which compressive and tensile strains generally increase and decrease the thermal conductivity, 14 respectively, molecular dynamics studies have suggested that both tensile and compressive strains reduce the thermal conductivities of graphene and MoS2.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…We could not uncover any meaningful correlation between strain and the thermal diffusivity from the experimental data. The spread in the strain between the de-vices estimated from the resonance frequency is no more than 0.4%, which should result in a spread in the thermal conductivity of approximately 3% [36]. The measured device-to-device spread is significantly larger and straindependence is thus not the cause of the observed variations.…”
Section: B Relation Between Mechanical and Thermal Propertiesmentioning
confidence: 84%
“…Small κ could jeopardize heat dissipation of TMD-based electronics, and techniques to enhance the cross-plane thermal conductivity are required. Previous theoretical studies of strain's effect on thermal conductivity in TMDs have reached inconsistent conclusions [38][39][40][41][42], and experimental studies have not yet been reported. Thus, exploring the tunability of thermal conductivity in TMDs with strain will not only have scientific significance, but also inform thermal management techniques in all TMD-based electronic devices.…”
mentioning
confidence: 96%